KAJIAN SIFAT FISIK, KIMIA, DAN BIOLOGI PADA TANAH BERPASIR DI BEBERAPA WILAYAH INDONESIA - Aprilia, Rennanti Lunnadiyah; Sukur, Sukur (Jurnal Agroteknologi (Agronu), 2022)
The growth, development and yield of plant production are influenced by soil properties, both physical, chemical and biological properties of the soil. The physical properties of the soil include texture, structure, consistency, soil moisture (the ability of the soil to hold water) and soil permeability. Soil chemical properties include soil pH, cation exchange capacity and nutrient content. Nutrient content, consisting of mineral and organic content including nitrogen, phosphorus, potassium and other materials. Biological properties of soil are microorganisms that decompose organic matter that live in the soil. To get optimal yields on sandy soil, a solution is needed to solve the problem of physical, chemical and biological properties of sandy soil. This study uses secondary data aimed at knowing the physical, chemical and biological conditions that exist in several coastal areas in Indonesia. The results obtained treatment recommendations to improve the physical, chemical and biological conditions of sandy soil so as to produce optimal plant production. Based on the data obtained, to improve the condition of the sandy soil, several soil amendments can be used, including using compost, manure, biochar, and nitrogen fixing. The results showed that the addition of soil amendments improved soil quality, especially on the physical properties of the soil where in sandy soil the most important thing was the ability of the soil to hold water and maintain available nutrients in the soil. The most important soil chemical properties are the availability of nutrients in the soil. The responses obtained vary, especially in sandy soils and depend on the commodity of the plant. Keywords: biological, physical, chemical, sandy soil, soil